The 2dF QSO Redshift Survey - XV. Correlation analysis of redshift-Space distortions - Angela, J; Outram, P; Shanks, T; Boyle, B; Croom, S; Loaring, N; Miller, L; Smith, R (2005)
We analyse the redshift-space (z-space) distortions of QSO clustering in the 2dF QSO Redshift Survey (2QZ). To interpret the z-space correlation function, xi(sigma,pi), we require an accurate model for the QSO real-space correlation function, xi(r). Although a single power-law xi(r) model fits the projected correlation function (wp(sigma)) at small scales, it implies somewhat too shallow a slope for both wp(sigma) and the z-space correlation function, xi(s), at larger scales > 20 h^(-1) Mpc. Motivated by the form for xi(r) seen in the 2dF Galaxy Redshift Survey (2dFGRS) and in standard LCDM predictions, we use a double power-law model for xi(r) which gives a good fit to xi(s) and wp(sigma). The model is parametrized by a slope of gamma=1.45 for 1